2017
DOI: 10.1080/07352166.2017.1343632
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighborhood ethnic diversity and social outcomes: Context-dependent effects within a postindustrial city undergoing regeneration

Abstract: This article examines whether perceived neighborhood ethnic diversity is associated with a range of social outcomes in a postindustrial city undergoing regeneration. The research included a survey in 3 types of deprived area in Glasgow: those undergoing regeneration, those directly adjoining regeneration areas, and those further removed from regeneration areas. In areas undergoing regeneration, perceived diversity was positively associated with many residential, cohesion, safety, and empowerment outcomes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Lastly, the results showing positive effects for the areas surrounding the larger regeneration areas, which are in receipt of relocated residents and a limited amount of new housing, indicate a number of things: that shorter-distance moves may be positive for mental health and wellbeing, echoing findings from earlier eras of relocation where longer distances resulted in feelings of loss of community (Young and Willmott, 1957); that 'negative spillover effects' are not an inevitable corollary of regeneration (Kleinhans and Varaday, 2011); and that social compositional changes brought about by regeneration, in this case an increased presence of ethnic minority residents relocated from tower blocks (Lawson and Kearns, 2017), are not necessarily negative, as is often assumed (McCartney et al, 2017), and indeed may be positive where a community lacked cohesion previously (Kearns and Whitley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the results showing positive effects for the areas surrounding the larger regeneration areas, which are in receipt of relocated residents and a limited amount of new housing, indicate a number of things: that shorter-distance moves may be positive for mental health and wellbeing, echoing findings from earlier eras of relocation where longer distances resulted in feelings of loss of community (Young and Willmott, 1957); that 'negative spillover effects' are not an inevitable corollary of regeneration (Kleinhans and Varaday, 2011); and that social compositional changes brought about by regeneration, in this case an increased presence of ethnic minority residents relocated from tower blocks (Lawson and Kearns, 2017), are not necessarily negative, as is often assumed (McCartney et al, 2017), and indeed may be positive where a community lacked cohesion previously (Kearns and Whitley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be consistent with Mulder's (2012) argument that population influences housing via housing demand, while housing influences the number of people and households via attraction of migrants. In addition, the study by Kearns and Whitley (2018) found that perceived ethnic diversity was associated with safety and control, and thus attributed this to the positive neighborhood cohesion outcomes; and positive neighborhood cohesion outcomes are attributes of resilient cities. It is suggested that building social cohesion in a community can manifest itself as a result of strong social networks (Carpenter, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Conflict theory accounts for the negative association between diversity and trust most often found in the U.S., but by no means restricted to here (Alesina & La Ferrara, 2002;Costa & Kahn, 2003;Putnam, 2007). Results ranging from Britain (Laurence, Schmid, & Hewstone, 2018) to Sweden (Goldschmidt, Hallsten, & Rydgren, 2017) to Scotland (Kearns & Whitley, 2017) to Germany (Gundelach & Traunmüller, 2014) suggest that diversity has a negative effect on trust internationally. "The more we are brought into physical proximity with people of another race or ethnic background, the more we stick to our own and the less we trust the other" (Putnam, 2007, p. 142).…”
Section: Proximity To Diversitymentioning
confidence: 99%